Comparative Evaluation Of Mineral & Crystalline Pattern Of Dfdba & Differnt Cbr Scaffolds - M. Khairnar, Shreyasi; N, Ravikiran; Porwal, Kratika Baldua; Vyas, Vijeta; Rizvi, Alquama; Kamble, Ashlesha (Journal of Neonatal Surgery, 2025)
The outcomes of phase I periodontal treatment are confined to the reduction of inflammatory responses and the restoration of soft tissue; however, this phase does not achieve the restoration and regeneration of the hard tissue components of the periodontium. Thus we need special techniques like use of bone grafts to plays crucial post-operative postive role in this treatment. Thus in this study we have used XRD & EDS mapping to assess the difference of DFDBA, SMCC & MCS in their mineral content and crystalline pattern. Where, DFDBA was 0.7×0.7 cm, SMCC was 0.8×0.9 cm and MCS was 0.5×0.5 cm dimention respectively. Upon comparing the surfaces of DFDBA, SMCC, and MCS revealed significant differences in their roughness, porosity, mineral content, and CA/P ratio. Thus, to conclude our research, we can say that, although SMCC demonstrates enhanced bioactivity, integration attributed to its Ca : P & open porosity, yet DFDBA remains a viable option for scenarios that require enhanced porosity & osteoconductivity.